Consumer preferences for the use of an innovative digital menu solution in public food service settings in four European countries. (December 2021) - Chen, Yang; Perez-Cueto, Federico J.A.; Giboreau, Agnès; Mavridis, Ioannis; Hartwell, Heather
Highlights: Consumers from 4 countries were introduced to a FoodSMART app. Consumer preferences for the use of a technical menu solution was investigated. Canteen food quality is the top priority for consumers' decision-making. Food hygiene, sustainability, safety, and freshness were the highest priority. Preferences for other criteria varied from country to country. Abstract: Consumer preferences for the use of an innovative menu solution in public canteen services in the UK, Greece, France, and Denmark were investigated. Participants from both control and test groups were first introduced to the FoodSMART app through a video clip as well as verbal explanations. The control group filled a questionnaire evaluating their preferences for the use of a technical menu solution in public food services straight away, whereas the test group had the opportunity to experience the app adapted to a daily canteen menu in real-time before completing the questionnaire. The data collected was examined in both country-specific and collected manners. Participants in all four countries valued the canteen food quality the most, especially food hygiene, sustainability, safety, and freshness. Their preferences for other features such as app functions, information provision, and ethical issues varied in different countries. The knowledge gained from this study provides valuable lessons for the future design of a food-quality-focused digital menu solution in canteen services adapted to the specific country and population context to promote informed consumer food choices.